The role of prophylactic antibiotics in hepatitis B virus-related acute-on-chronic liver failure patients at risk of bacterial infection: a retrospective study - Xiao-Qin Liu; Xue-Yun Zhang; Yue Ying; Jian-Ming Zheng; Jian Sun; Wen-Hong Zhang; Ji-Ming Zhang; Yu-Xian Huang (BMC, 2021)
Abstract Background Acute-on-chronic liver failure (ACLF) is characterized by an excessive systemic inflammatory response and organ failure and has high mortality. Bacterial infections (BIs) worsen the clinical course of ACLF and carry a poor prognosis in ACLF patients. The efficacy of third-generation cephalosporins has been challenged in recent years. The aim of this study was to characterize the difference between ACLF patients with and without BIs and to provide a reference for medical intervention. Methods A total of 140 patients with hepatitis B virus-related ACLF (HBV-ACLF) hospitalized at the Department of Infectious Diseases, Huashan Hospital, Fudan University (Shanghai, China) between May 2013 and January 2020 were enrolled. Mann-Whitney U test was used to compare the baseline characteristics of HBV-ACLF patients with and without BIs. Univariate and multivariate analyses were performed to find predictors of BIs. The characteristics of BIs and the role of prophylactic antibiotics were profiled. Results A total of 97 episodes of BIs occurred in patients during the course of HBV-ACLF. Patients with and without BIs differed in clinical characteristics. The incidence of BIs showed a positive correlation with the ACLF grade (P = 0.003) and the clinical course (P = 0.003). The 90-day transplant-free survival of patients with BIs was lower than those without BIs (P < 0.0001). Patients administered prophylactic antibiotics showed a lower incidence of BIs and had a higher transplant-free survival probability than those who did not (P = 0.046). No statistical differences in antibiotic efficacy between third-generation and other antibiotics were observed (P = 0.108). Conclusions BIs affected the clinical course and prognosis of patients with HBV-ACLF. Prophylactic antibiotics were of potential clinical importance in the prevention of BIs and improving the clinical course and prognosis in HBV-ACLF patients. Third-generation cephalosporins were qualified for use in antibiotic prophylaxis.